Child-caregiver interaction in two remote Indigenous Australian communities - Vaughan, Jill; Wigglesworth, Gillian; Loakes, Deborah; Disbray, Samantha; Moses, Karin (Frontiers in Psychology, 2015)
This paper reports on a study in two remote multilingual Indigenous Australian communities: Yakanarra in the Kimberley region of Western Australia and Tennant Creek in the Barkly region of the Northern Territory. In both communities, processes of language shift are underway from a traditional language (Walmajarri and Warumungu respectively) to a local creole variety (Fitzroy Valley Kriol and Wumpurrarni English respectively). The study focuses on language input from primary caregivers to a group of preschool children, and on the children’s productive language. The study further highlights child-caregiver interactions as a site of importance in understanding the broader processes of language shift. We use longitudinal data from two time-points, approximately two years apart, to explore changes in adult input over time and developmental patterns in the children’s speech. At both time points, the local creole varieties are the preferred codes of communication for the dyads in this study, although there is some use of the traditional language in both communities. Results show that for measures of turn length (MLT), there are notable differences between the two communities for both the focus children and their caregivers. In Tennant Creek, children and caregivers use longer turns at Time 2, while in Yakanarra the picture is more variable. The two communities also show differing trends in terms of conversational load (MLT ratio). For measures of morphosyntactic complexity (MLU), children and caregivers in Tennant Creek use more complex utterances at Time 2, while caregivers in Yakanarra show less complexity in their language at that time point. The study’s findings contribute to providing a more detailed picture of the multilingual practices at Yakanarra and Tennant Creek, with implications for understanding broader processes of language shift. They also elucidate how children’s language and linguistic input varies diachronically across time. As such, we contribute to